Peningkatan Berpikir Kritis Model Inkuiri Berbantuan Media Kotak Berpikir Tema 7 Kelas IV SD Karanganyar 2 - Linda Kurniasari; Fina Fakhriyah; Eko Widianto (Journal Prakarsa Paedagogia, 2020)
This study aims to describe the students’ critical thinking skills in the material taught by the beauty of diversity in my country which includes ethnic, linguistic and traditional clothing in Indonesia through the inquiry model. This type of research is a classroom action research that will be carried out in two cycles, with data collection used in this study is a test and non-test constinting of interview, observation and documentation. Analsis of the data used in this research is quantative and qualitative data analysis. The subject in this study were 25 students consisting of 15 female students and 10 male students. Based on the result of the study it can be concluded that the increase in students ‘critical thinking skills through inquiry models assisted with Indonesian box thinking media on theme 7 grade IV SD Karanganyar 2 on prasiklus test result showed a percentage of classical completeness 66,92% had an increase in students’ critical a significant increase with an average score of 85,24%. Based on these studies it can be concluded that the use of inquiry model assisted b Indonesian box thinking media can improve students’ critical thinking skills on theme 7.